Supramolecular Coronation of Platinum(II) Complexes by Macrocycles: Structure, Relativistic DFT Calculations, and Biological Effects - Sojka, Martin; Chyba, Jan; Paul, Shib Shankar; Wawrocka, Karolina; Hönigová, Kateřina; Cuyacot, Ben Joseph R; Castro, Abril C; Vaculovič, Tomáš; Marek, Jaromír; Repisky, Michal; Masařík, Michal; Novotný, Jan; et al. (Inorganic chemistry, 2021)
Platinum-based anticancer drugs are actively developed utilizing lipophilic ligands or drug carriers for the efficient penetration of biomembranes, reduction of side effects, and tumor targeting. We report the development of a supramolecular host-guest system built on cationic platinum(II) compounds bearing ligands anchored in the cavity of the macrocyclic host. The host-guest binding and hydrolysis process on the platinum core were investigated in detail by using NMR, MS, X-ray diffraction, and relativistic DFT calculations. The encapsulation process in cucurbit[7]uril unequivocally promotes the stability of hydrolyzed dicationic cis-[PtII(NH3)2(H2O)(NH2-R)]2+ compared to its trans isomer. Biological screening on the ovarian cancer lines A2780 and A2780/CP shows time-dependent toxicity. Notably, the reported complex and its β-cyclodextrin (β-CD) assembly achieve the same cellular uptake as cisplatin and cisplatin@β-CD, respectively, while maintaining a significantly lower toxicity profile.
Keywords: viabilita buněk; makrocyklické sloučeniny; makromolekulární látky; protinádorové látky; Cell Proliferation; Drug Screening Assays, Antitumor; molekulární struktura; Molecular Structure; Cell Survival; Density Functional Theory; Organoplatinum Compounds; Macrocyclic Compounds; teorie funkcionálu hustoty; lidé; Humans; nádorové buňky kultivované; proliferace buněk; screeningové testy protinádorových léčiv; Tumor Cells, Cultured; Macromolecular Substances; organoplatinové sloučeniny; Antineoplastic Agents